YIV-818-A: a novel therapeutic agent in prostate cancer management through androgen receptor downregulation, glucocorticoid receptor inhibition, epigenetic regulation, and enhancement of apalutamide, darolutamide, and enzalutamide efficacy - Lam, Wing; Arammash, Mohammad; Cai, Wei; Guan, Fulan; Jiang, Zaoli; Liu, Shwu-Huey; Cheng, Peikwen; Cheng, Yung-Chi (Frontiers in Pharmacology, 2023)
Prostate cancer is the second leading cause of cancer death among men in the United States.Androgen or Androgen receptor (AR) targeted therapy is a strategy for the treatment of prostate cancer, however, long-term treatment with androgen deprivation therapy inevitably leads to the development of Castration-Resistant Prostate Cancer (CRPC). AR variants and glucocorticoid receptor (GR) are two key factors to promote resistance to AR-targeting therapies in CRPC patients. Developing a multi-targeted drug that can inhibit both the AR variant and GR action could help overcome drug resistance. Through our STAR (Signal, Transduction, Activity, and Response) Drug Discovery Platform, we studied the effects of three hundred medicinal plant extracts across 25 signaling pathways to identify a drug candidate. YIV-818-A was developed as a novel botanical drug candidate based on optimized water extracts of Rubia cordifolia (R.C.). YIV-818-A could inhibit Dihydrotestosterone (DHT) or Dexamethasone (DEX) induced luciferase activity of 22RV1 cells which were harboring ARE luciferase reporter. Using activity guided purification of YIV-818-A, Deoxybouvardin (RA-V) was identified as the key active compound for inhibiting AR and GR activities. R.C. collected from different sources had different quantities of RA-V. The potency of androgen receptor inhibition in various R.C. forms can be partially correlated to their corresponding levels of RA-V. YIV-818-A, RA-V and RA-VII (RA-V's analog) could effectively downregulate both AR and AR-V (AR splice variants) protein through inhibiting protein synthesis, impact the expression of AR target genes, and modify the epigenetic status of 22RV1 cells by reducing levels of Bromodomain and Extra-Terminal proteins (Brd2/Brd4) and H3K27Ac. Significantly, YIV-818-A and RA-V, and RA-VII demonstrated a synergistic effect with apalutamide, darolutamide, or enzalutamide, enhancing the inhibition of AR activity and suppression of 22RV1 cell growth. Notably, the co-administration of YIV-818-A and enzalutamide resulted in a marked reduction of 22RV1 tumor growth in vivo. In conclusion, YIV-818-A, RA-V and RA-VII offer a promising solution to overcoming drug resistance in CRPC by concurrently down-regulating AR protein, inhibiting GR function, and modulating critical epigenetic markers.Given the established safety profile of YIV-818-A, it holds potential as an effective chemopreventive agent and a potent anti-prostate cancer drug.